2021
DOI: 10.3390/genes12071005
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Reveals Diverse Molecular Characteristics between Endocardial and Aortic-Valvular Endothelium

Abstract: The variations in the protein profile of aortic-valvular (AVE) and endocardial endothelial (EE) cells are currently unknown. The current study’s objective is to identify differentially expressed proteins and associated pathways in both the endothelial cells. We used endothelial cells isolated from the porcine (Sus scrofa) aortic valve and endocardium for the profiling of proteins. Label-free proteomics was performed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Our proteomics analysis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…34 While aortic endothelial cells are commercially available and easy to obtain, recent studies have found that EECs have a unique proteomic signature, even in comparison to aortic endothelial cells, further demonstrating the necessity of including EECs in cardiac disease models. 6,14 This study also showed that EECs display the classical endothelial phenotypic characteristics, and that this phenotype is stable up to at least passage 15. EECs stained positively for typical markers of endothelial cells, but they were smaller and had a more elongated morphology than reported for other common endothelial cell lines.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…34 While aortic endothelial cells are commercially available and easy to obtain, recent studies have found that EECs have a unique proteomic signature, even in comparison to aortic endothelial cells, further demonstrating the necessity of including EECs in cardiac disease models. 6,14 This study also showed that EECs display the classical endothelial phenotypic characteristics, and that this phenotype is stable up to at least passage 15. EECs stained positively for typical markers of endothelial cells, but they were smaller and had a more elongated morphology than reported for other common endothelial cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…34 While aortic endothelial cells are commercially available and easy to obtain, recent studies have found that EECs have a unique proteomic signature, even in comparison to aortic endothelial cells, further demonstrating the necessity of including EECs in cardiac disease models. 6,14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative protein quantification of control and treated samples was performed using ESI-nano LC-MS/MS analysis [a nano ACQUITY UPLC ® chromatographic system (Waters) coupled with a Quadrupole Time-of-Flight (Q-TOF) mass spectrometer (SYNAPT-G2, Waters)] as described by Aneesh Kumar et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%